1987
DOI: 10.1073/pnas.84.11.3782
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduct frequency is not the major determinant of UV base substitution hot spots or cold spots in human cells.

Abstract: The role of UV radiation-induced photoproducts in initiating base substitution mutations in human cells was examined by measuring photoproduct frequency distributions and mutations in a supF tRNA gene on a shuttle vector plasmid transfected into DNA repair-deficient cells (xeroderma pigmentosum, complementation group A) and into normal cells. Frequencies of cyclobutane dimers and pyrimidine-pyrimidone (6-4) photoproducts varied by as much as 80-fold at different dipyrimidine sites within the gene. AU transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
112
2
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(124 citation statements)
references
References 18 publications
9
112
2
1
Order By: Relevance
“…Brash et al (39) have recently shown that in mammalian cells UV-induced mutational hot spots do not correlate with the frequency of photoproduct formation. Furthermore, repair processes may be of considerable importance since region-to-region and site-to-site variations in repair (40,41) and the fidelity of DNA polymerase (42) have been observed.…”
Section: G-c-at G-c-+a-t At-*t-a A*t--t-a G-c--+a-t G-c--mentioning
confidence: 99%
“…Brash et al (39) have recently shown that in mammalian cells UV-induced mutational hot spots do not correlate with the frequency of photoproduct formation. Furthermore, repair processes may be of considerable importance since region-to-region and site-to-site variations in repair (40,41) and the fidelity of DNA polymerase (42) have been observed.…”
Section: G-c-at G-c-+a-t At-*t-a A*t--t-a G-c--+a-t G-c--mentioning
confidence: 99%
“…The two types of DNA damage which are considered to be primarily responsible for the lethal and mutagenic effects of UV irradiation are the cyclobutane pyrimidine dimer (7,19) and the (6-4) pyrimidine-pyrimidone photoproduct (3, 10). Still, controversy exists over the relative importance of both types of lesions for cell killing and mutagenesis (4,6,13,16).It has been shown for cultured Chinese hamster and human cells that removal of dimers from the transcriptionally active dhfr gene is more rapid than for the genome overall (1, 2, 11) and that possibly even a strand specificity in DNA repair exists (12). Dimers were removed at a faster rate in human cells and to a larger extent in Chinese hamster ovary (CHO) cells from the transcribed strand from the amplified dhfr gene than from the nontranscribed strand.…”
mentioning
confidence: 99%
“…The two types of DNA damage which are considered to be primarily responsible for the lethal and mutagenic effects of UV irradiation are the cyclobutane pyrimidine dimer (7,19) and the (6-4) pyrimidine-pyrimidone photoproduct (3, 10). Still, controversy exists over the relative importance of both types of lesions for cell killing and mutagenesis (4,6,13,16).…”
mentioning
confidence: 99%
“…For example, the frequencies of CAA and AAA mutations are much greater at the 5′-TT site than at the 5′-CT site (Table 3, compare rows 1 and 2). This might indicate a greater capacity for DNA damage, since TTCPDs occur more often than CT-CPDs, combined with the knowledge that products can form at TT sites, but are unlikely at 5′-CT sites [28]. The increase in the proportion of CAA mutations is consistent with the specificity of the TT product (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, 5′-CT dimers may present a different obstacle for DNA polymerase, altering the base selection process. Since products probably do not readily form at 5′-CT sequences [7,28], the premutagenic lesion is likely a CPD.…”
Section: Discussionmentioning
confidence: 99%